Perfil teórico/metodológico do desenvolvimento de sequências didáticas para o ensino de química descritas em produções acadêmicas da região Nordeste - Nogueira, Fabiane Brandão (2019)
With the difficulties faced by professors and students of Chemistry, it is increasingly necessary for teachers to apply innovative teaching activities in the classroom, which lead students to evolve concepts related to curricular content and their abilities and attitudes. However, it is important that teachers plan activities in order to instruct students appropriately so that they can achieve the goals proposed in pedagogical planning (CARVALHO and PEREZ, 2001). From this perspective, interest in the development and diffusion of Didactic Sequences (SD) in Teaching Chemistry has grown significantly throughout Brazil. Aiming to research on the progress of this didactic trend in the Northeast of the country and to draw a theoretical/ methodological profile of these Didactic Sequences, in this study 18 dissertations and two doctoral theses were analyzed. These works were defended in Post-Graduate Programs in Science and Mathematics Teaching between 2000 and 2017. This research also aims to contribute to the elaboration of other SD in the Chemistry area, optimize the time of elaboration of them and disseminate the themes already covered in those published. The collection of these documents was done through the Database of Theses and Dissertations (BDTD) and repositories of electronic documents of the universities of the Northeast. The descriptors used were: Didactic Sequence; Chemistry; and Sequence of Teaching Learning. The methodology of the research is anchored in the bibliographic research, of an exploratory nature. The Didactic Sequences were grouped based on the respective theoretical / methodological foundations presented in the documents analyzed. Considering the obtained data it can be verified that there is a significant number of experiments introduced as part of some of the SD activities; another highlight of the research is given to the fact that few are concerned with assigning a theoretical basis based on the most established authors in the area of SD elaboration and validation. Therefore, many are not validated or at least they are not in the way that the authors of the area guide and that in this work was considered as more complete method. This form of elaboration and validation can weaken both the teaching and learning process proposed in the interactions, and in the potentiality of a Didactic Sequence. By tracing the profiles of these SDs from the Northeast region, it has been estimated that they were designed for high school students, with a mean of between 8 and 15, and were considered by most researchers as a method of evaluation of SD both before and after test, mostly done through questionnaire. For the complementary reasoning of the Sequences, Contextualization was presented, or focus was given to the CTS approach or to Significant Learning Theory. One trend that appears a bit timid is the History of Science. The authors' view of seven SDs addressed in this dissertation is also presented in this paper, from their response to a questionnaire of nine open questions. In this perspective, among some possible findings, their consensus was related to the fact that the elaboration and application of SD can act as a motivating factor in the teaching and learning process for the Chemistry discipline.